Gandhi's African legacy: Phoenix settlement 1904 - 2024 - Muthien, Bernedette (New Agenda: SA Journal of Social and Economic Policy, 2025)
On the afternoon of Saturday 3 October, Uma Dhupelia-Mesthrie’s book, Gandhi’s African Legacy Phoenix Settlement: 1904-2024. A History Through Letters, was launched at the Desmond and Leah Tutu Legacy Centre Foundation1 in Cape Town under the theme of “Talking Rights”. This launch was immediately followed by the Insurrection Ensemble’s multi-media production, Must Gandhi Fall?, under the theme of “Performing Rights”, at the historic theatre2 at the District SixHomecoming Centre around the corner. These two successive events are inextricably connected. They were part of the Living Rights Festival with its focus on intersectional justice and realising constitutional rights through multi-genre arts.